Simulation of Contaminants Transport from a Dumpsite into Shallow Aquifer of the Upper Deltaic Plain Deposits, Western Niger Delta - Aweto, K. E.; Ovwamuedo, G. (Journal of Scientific Research, 2023)
Dumpsites are a copious point source of groundwater pollution in the Niger Delta. The objective of this study seeks to assess contaminants transported from a dumpsite around Ekpan into groundwater. Dumpsite leachate and groundwater samples were collected for analysis, and the Modular 3D Solute Transport Model (MT3D) was used to evaluate the impact of leachate on the quality and flow direction of groundwater. The chemical analyses of leachate samples showed significant potential to contaminate groundwater. The pH of greater than 7 and BOD5/COD ratio of less than 0.1 indicated that the dumpsite is old with stabilized leachate. Groundwater models showed that the dumpsite has the propensity for Na and TDS increasing to 1500 and 3700 mg/L respectively after 10 years. The contaminants infiltrate into successive layers beneath the dumpsite and spread laterally in the direction of groundwater flow (southwestern direction). This study revealed that groundwater near the dumpsite did show some significant contamination. A pattern of decreasing concentration of contaminants with distance from the dumpsite was observed due to natural attenuation.